PEMBELAJARAN SAINS BERBASIS EKOLITERASI MELALUI PENANAMAN TOGA UNTUK MENUMBUHKAN LITERASI SAINS SISWA MADRASAH IBTIDAIYAH - Aftina, Naila; Hanik, Elya Umi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Science education in elementary schools still tends to be theoretical and has not optimally utilized the environment as a learning resource. This study aims to describe the implementation of eco-literacy-based science education through the cultivation of Family Medicinal Plants (TOGA), analyze its effectiveness in fostering students' science literacy, and identify the supporting and inhibiting factors for its implementation at MI NU Tarbiyatul Banat. The research employs a descriptive qualitative approach using a case study method through observations, interviews, and documentation. The results indicate that eco-literacy-based science education through TOGA cultivation can be effectively and contextually implemented. Students' science literacy develops across context, knowledge, competencies, and attitudes. Supporting factors include student motivation, active involvement, and teachers' roles, while inhibiting factors include time constraints, weather conditions, and plant maintenance. Eco-literacy-based learning has the potential to be a sustainable alternative for science education.